Entering Guanxi: A Business Ethical Dilemma in Mainland China? - Su, Chenting (Journal of business ethics, 2001)
This paper represents an effort to distinguish between two types of guanxi prevalent in mainland China: favor-seeking guanxi that is culturally rooted and rent-seeking guanxi that is institutionally defined. Different rules of maneuvering the two types of guanxi are identified in light of Chinese cultural and business ethics. Strategies for entering guanxi in mainland China are also suggested.